PENGEMBANGAN BUDIDAYA UDANG VANAME (Penaeus vannamei) EBERDASARKAN KUALITAS AIR DI PULAU OBI, PROVINSI MALUKU UTARA, INDONESIA - Tamrin, Tamrin; Abdullah, Taufiq; Aris, Muhammad (JARI : Jurnal Akuakultur Rawa Indonesia, 2023)
The potential of aquaculture in North Maluku Province, especially the Obi islands, has not been maximally utilized. One commodity that can be developed is Whiteleg shrimp. This commodity is a major aquaculture commodity with important economic value. Analysis of the suitability of waters for Whiteleg shrimp cultivation is an early stage of activity that greatly determines the success of cultivation. Therefore, this study aims to assess the suitability of waters for the development of Whiteleg shrimp aquaculture on the island of Obi. This study was conducted in the waters of Soligi, Kawasi, Baru, Akegula, Laiwui, Buton, Jikotamo, Sambiki, and Anggai of Obi Island, South Halmahera Regency. Water quality parameters observed were temperature, brightness, depth, current speed, salinity, pH, dissolved oxygen, nitrate, and phosphate. Each parameter was then analyzed by land suitability. The results showed that the waters of Obi Island have the potential for the development of Whiteleg shrimp cultivation based on the observed water quality parameters. This study concludes that the waters of Obi Island, South Halmahera Regency, North Maluku Province can be used to develop Whiteleg shrimp farming. The location of the waters has the criteria of suitability is very suitable for the cultivation of Whiteleg shrimp.